FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR DI PRAKTIK MANDIRI BIDAN (PMB) IRMA SURYANI KOTA PRABUMULIH TAHUN 2023 - Eka Juniarty; Diah Ayu Lestari; Pera Mandasari (LPPM STIKes Mitra Adiguna, 2024)
According to the World Health Organization (WHO), in 2019 the infant mortality rate (IMR) was 27 deaths per 1000 live births. The infant mortality rate, which is quite high in the world, can actually be avoided by giving breast milk, especially colostrum. The aim of the study was to determine the factors associated with giving colostrum to newborns at the Independent Midwife Practice (PMB) Irma Suryani Prabumulih City in 2023. The research method is analytic in nature, using a cross sectional approach. The population of this study were all mothers who gave birth to babies 0-28 days at the Independent Midwife Practice (PMB) Irma Suryani Prabumulih City in 2023. The number of samples in this study were 36 respondents. Sampling using Accidental sampling method. The research instrument is a questionnaire. The results of the study based on univariate analysis found that out of 36 respondents there were 10 respondents (27.8%) who did not give colostrum and 26 respondents (72.2%) who did give colostrum, there were 26 respondents (72.2%) who had knowledge good and 10 respondents (27.8%) had less knowledge, there were 23 respondents (63.9%) who had low risk parity and 13 respondents (36.1%) had high risk parity, there were 27 respondents (75%) who received family support and 9 respondents (25%) did not receive family support. From the bivariate analysis it was known that of the 26 respondents who had good knowledge, there were 24 respondents (66.7%) who gave colostrum, while of the 12 respondents with high risk parity, there were 4 respondents (11.1%) who gave colostrum, of the 27 respondents who received family support there were 24 respondents (66.7%) giving colostrum In conclusion, there is a significant relationship between knowledge and giving colostrum with a P-value of 0.000 <? 0.05, there is a significant relationship between parity and giving colostrum with a P-value of 0.001 <0.05, there is a significant relationship between family support and giving colostrum with a value Value 0.000 < ? 0.05,